TEOREMA TITIK TETAP UNTUK PEMETAAN KANNAN PADA RUANG METRIK MODULAR TERITLAK - Harini, Lusi (Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2019)
In this paper, we will discuss about fixed point theorems in generalized modular metric space for Kannan-$D_λ$ type mapping. The existence of the fixed point of this mapping is guaranteed by providing that the mapping domain is a -finite set and the Kannan-$D_λ$ mapping constant $α\in(0,1/2)$ satisfied $α K<1$ where K is a constant from the axiom of generalized modular metric space.